Pengaruh Pemberian Pentoksifilin Terhadap Perubahan Kadar Platelets Activating Factor pada Cedera Reperfusi-Iskemik Tungkai Akut - Daf Juzar; Manoefris Kasim; Nani Hersunarti; RWM Kaligis (The Indonesian Heart Association, 2007)
Background. In Acute limb ischemia reperfusion causes further damage to the ischemic tissue through local compartment syndrome, and systemic syndrome: multiorgan dysfunction and failure. Several method and attempt had been studied and performed to prevent and attenuate reperfusion injury such as, ischemic preconditioning, antioxidant, and anti-cytokine therapy, but their clinical benefit were not satisfactory. Pentoxifylline (PTX) a nonspesifik phosphodiesterase derivate of xanthine has emerged as a promising agent that may attenuate inflammation response through several mechanism. However, studies on PTX and its function to prevent and attenuate inflammation response through attenuating Platelet-Activating Factor (PAF) in acute limb ischemic were not consistent. The aim of this study is to investigate the effect of PTX on PAF in rabbits with acute limb ischemic-reperfusion injury.Methods and results.Acute limb Ischemia were performed by direct occlusion of the left femoral artery of 10 New Zealand White male rabbit using non traumatic clamp, and followed by releasing the clamp after 3 hours of occlusion. The rabbits were randomly separated into 2 groups of five (PTX group and control group). The PTX group was given PTX 40 mg/kg bolus half an hour prior to reperfusion, followed by maintenance dose 1 mg/kg/hour until 2 hour post reperfusion, while the control group was given normal saline solution with comparable volume and rate administration. Level of PAF were measured after 2.5 hour of ischemic period and after 2 hours of reperfusion period. After 2.5 hours of ischemic period, the mean PAF levels did not show any significant difference (p=0.754), the mean PAF level of PTX group 13.09±0.41 pg/mL, while the control group 13.38±0.28 pg/mL. After 2 hours period of reperfusion, there were significant differences of mean PAF level between the two groups (p=0.009). The mean PAF level in the control group increase by 12.11±0.79 to became 25.5±0.78 pg/dL, while the mean PAF level of the PTX group decrease by 1.73±1.1 pg/mL and became 11.36±0.78 pg/mL.Conclusions. Pentoxifylline attenuate the production Platelet-Activating Factor level in rabbits with acute limb ischemic-reperfusion injury.